Seismic performance evaluation of a steel tubular bridge pier in a five-span continuous girder bridge system. (June 2021) - Wang, Zhanfei; Ren, Hao; Shen, Qihang; Sui, Weining; Zhang, Xin
Abstract: The seismic performance of a steel tubular bridge pier in a five-span continuous girder bridge system was evaluated through dynamic non-linear time-history analysis under strong ground motions. The seismic performance of the hollow steel tubular (HST) and partially concrete-filled steel tubular (PCFST) bridge piers was assessed with different eccentricities of superstructure. Considering the variation of ground classification under rare earthquakes, six seismic waves were input. The analytical results indicate that the eccentricity of superstructure has little effect on the maximum displacement response of the HST bridge piers and the PCFST bridge piers under ground motion excitations in the longitudinal ( LG ) direction; however, under the ground motion excitations in the transverse ( TR ) direction, the maximum displacement response of the bridge piers increases when the eccentricity ( e / H ) increases from 0 to 0.2, which implies that eccentricity affects the seismic response of the two types of piers. Both in the LG direction and TR direction, the HST piers have reached their yield strengths; stress concentration and local buckling were observed around the plastic hinge zone and the load bearing capacity decreases. Although the PCFST piers entered the elasto-plastic range, the expansion of local buckling deformation of the steel tubular column has been restrained by the concrete in-fill. According to the simulated results, the PCFST pier exhibits high ductility and bearing capacity, which can improve the seismic performance of the bridge system.